2013
DOI: 10.1172/jci62742
|View full text |Cite
|
Sign up to set email alerts
|

Patients with type 1 diabetes exhibit altered cerebral metabolism during hypoglycemia

Abstract: Patients with type 1 diabetes mellitus (T1DM) experience, on average, 2 to 3 hypoglycemic episodes per week. This study investigated the effect of hypoglycemia on cerebral glucose metabolism in patients with uncomplicated T1DM. For this purpose, hyperinsulinemic euglycemic and hypoglycemic glucose clamps were performed on separate days, using [1-13 C]glucose infusion to increase plasma 13 C enrichment. In vivo brain 13 C magnetic resonance spectroscopy was used to measure the time course of 13 C label incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 47 publications
0
33
0
Order By: Relevance
“…There was no significant difference in brain glucose concentrations between the nondiabetic persons and the patients with type 1 diabetes in the study by van de Ven and colleagues, 45 suggesting no difference in blood-to-brain glucose transport. Assuming the patients with type 1 diabetes did not have HAAF (epinephrine responses in these patients were similar to those in nondiabetic persons, and symptoms of hypoglycemia were not reported), commentators suggested that blood-to-brain glucose uptake might have been increased in patients with HAAF, if they had been included in the study.…”
Section: Brain Fuel-transport Hypothesismentioning
confidence: 86%
See 2 more Smart Citations
“…There was no significant difference in brain glucose concentrations between the nondiabetic persons and the patients with type 1 diabetes in the study by van de Ven and colleagues, 45 suggesting no difference in blood-to-brain glucose transport. Assuming the patients with type 1 diabetes did not have HAAF (epinephrine responses in these patients were similar to those in nondiabetic persons, and symptoms of hypoglycemia were not reported), commentators suggested that blood-to-brain glucose uptake might have been increased in patients with HAAF, if they had been included in the study.…”
Section: Brain Fuel-transport Hypothesismentioning
confidence: 86%
“…The rate of blood-to-brain glucose transport exceeds the rate of cerebral glucose metabolism even at plasma glucose concentrations of 65 mg per deciliter (3.6 mmol per liter) in humans. 30,42 Extrapolation of the linear relationship between plasma and brain glucose concentrations, the latter measured with 13 C magnetic resonance spectroscopy, in nondiabetic persons and patients with type 1 diabetes during euglycemia and hypoglycemia, as reported by van de Ven and colleagues, 45 suggests that the plasma glucose concentration at which the brain glucose concentration would become zero -at which point brain glucose metabolism would have to decrease -is less than 36 mg per deciliter (2.0 mmol per liter). An increase in blood-to-brain glucose transport would not increase brain glucose metabolism unless it shifted from below to above that unknown, but seemingly low, glycemic threshold.…”
Section: Brain Fuel-transport Hypothesismentioning
confidence: 95%
See 1 more Smart Citation
“…van de Ven et al 3 reported that type 1 diabetes mellitus patients showed altered cerebral glucose metabolism during hypoglycemia compared with healthy controls. In their previous study, they used 13 C magnetic resonance spectroscopy to explore cerebral glucose metabolism during hypoglycemic glucose clamp in healthy subjects and evaluated the tricarboxylic acid cycle flux (V TCA ).…”
mentioning
confidence: 99%
“…Although most type 1 diabetes mellitus patients experience hypoglycemia, the frequency of hypoglycemia is not related to a higher risk of cognitive impairment. On the basis of this result, van de Ven et al 3 hypothesized that the brain physiologically adapts to protect itself from hypoglycemia. To test this hypothesis, they carried out euglycemic and hypoglycemic glucose clamp on type 1 diabetes mellitus patients and compared their cerebral glucose metabolism with that of healthy subjects.…”
mentioning
confidence: 99%